A new species of the endemic Chilean leafhopper genus Chileanoscopus (Hemiptera: Cicadellidae: Idiocerinae) - Xue, Qingquan; Mckamey, Stuart H.; Zhang, Yalin (Zootaxa, 2017)
A new species, C. serrulatus sp. nov. is described and illustrated from Chile. A redescription of this genus is provided together with a key to species for males.